The Comparison of Distance Methods on The On-Demand Ambulance Application - Apriandy Angdresey; Vivie Deyby Kumenap; Phil Anggara Everhard Bawole (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2023)
The on-demand ambulance is an application service that can be used to connect hospital ambulances or NGOs with people who need ambulance services. In this application, there is a geolocation feature service that is implemented with the distance calculation method, so that the feature gets the optimal distance with high accuracy. There are 3 distance search methods used in testing the distance search method, namely the haversine method, the Euclidean method, and the spherical triangle law of the cosine method. This study was conducted by utilizing data collected from the Google Maps API and obtained an accuracy of 100% for the haversine and spherical triangle law of cosine methods, while the accuracy was 89.95% for the Euclidean method. Keywords—Distance Method; Haversine; Euclidean, Spherical Triangle Law of Cosine